Individuating Faces and Common Objects Produces Equal Responses in Putative Face-Processing Areas in the Ventral Occipitotemporal Cortex - Haist, Frank; Lee, Kang; Stiles, Joan (Frontiers in Human Neuroscience, 2010)
Controversy surrounds the proposal that specific human cortical regions in the ventral occipitotemporal cortex, commonly called the fusiform face area (FFA) and occipital face area (OFA), are specialized for face processing. Here, we present findings from a fMRI study of identity discrimination of faces and objects that demonstrates the FFA and OFA are equally responsive to processing stimuli at the level of individuals (i.e., individuation), be they human faces or non-face objects. The FFA and OFA were defined via a passive viewing task as regions that produced greater activation to faces relative to non-face stimuli within the middle fusiform gyrus and inferior occipital gyrus. In the individuation task, participants judged whether sequentially presented images of faces, diverse objects, or wristwatches depicted the identical or a different exemplar. All three stimulus types produced equivalent BOLD activation within the FFA and OFA; that is, there was no face-specific or face-preferential processing. Critically, individuation processing did not eliminate an object superiority effect relative to faces within a region more closely linked to object processing in the lateral occipital complex (LOC), suggesting that individuation processes are reasonably specific to the FFA and OFA. Taken together, these findings challenge the prevailing view that the FFA and OFA are face-specific processing regions, demonstrating instead that they function to individuate -- i.e., identify specific individuals -- within a category. These findings have significant implications for understanding the function of a brain region widely believed to play an important role in social cognition.